ASSESSMENT METHOD FOR NEW SUSTAINABILITY INDICATORS PROVIDING PANDEMIC RESILIENCE FOR RESIDENTIAL BUILDINGS - Tokazhanov, Galym; Tleuken, Aidana; Guney, Mert; Turkyilmaz, Ali; Karaca, Ferhat (MethodsX, 2021)
The method presented in this paper aims to support the sustainability assessment methods of residential buildings under pandemic conditions. The main purpose of the study is to review existing criteria of the well- known assessment tools and then to suggest a set of assessment measures for the emerging pandemic-resilient indicators. Current sustainability assessment methodologies mostly focus on the conventional sustainability pillars (Environmental, Social, Economic), whereas the proposed emerging sustainability assessment indicators include changes in sustainability requirements brought by the current pandemic. Firstly, a set of indicators with possible measures was identified; then, we reviewed several existing green building certification systems to identify their gaps and developed a foundation for each indicator. Finally, several round table discussions involving various stakeholders (e.g., engineers, designers, health care experts, academics) were conducted to consolidate the identified measures. The findings of the present study indicate that certain pandemic-resilient indicators are not fully addressed by existing assessment tools, pointing out the importance of the development of new measures to make them more suitable to use under pandemic conditions. Thus, the present study contributes to the building assessment methods by proposing a set of emerging assessment indicators with measures, which can be used by various professionals that would contribute to more sustainable buildings in upcoming pandemics
Keywords: Type of access: Open Access; Sustainability; COVID-19; Residential buildings; Green building